Position of The Investigation Termination Order (SP3) By The Police From The Perspective of Legal Certainty - Viermann Banjarnahor; Zainal Abidin pakpahan; Muhammad Yusuf Siregar (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The Investigation Termination Order (SP3) is an important instrument in the Indonesian criminal justice system, granted to investigators to terminate an investigation due to insufficient evidence, non-criminal events, or termination by law as stipulated in Article 109 paragraph (2) of the Criminal Procedure Code. This authority is directly related to the principle of legal certainty, which demands clarity, order, and protection for every individual facing the legal process. In practice, the SP3 serves to provide certainty of legal status for suspects to avoid criminalization or protracted investigations without adequate basis. However, the implementation of the SP3 often raises problems, especially when it is deemed non-transparent or has the potential for abuse by law enforcement officers. This can affect public trust in the Police institution and create uncertainty for victims or reporters. This research uses a normative juridical approach by examining laws and regulations, legal doctrine, and court decisions related to pretrial as an instrument of judicial control over the validity or invalidity of the issuance of the SP3. The analysis shows that although SP3 is a legal and necessary mechanism to maintain the effectiveness and accountability of investigations, its implementation still faces various challenges, such as inconsistent standards of evidence, minimal internal oversight, and limited public access to pretrial mechanisms. Therefore, strengthening measures are needed through increased transparency, standardization of investigation termination procedures, and optimization of the oversight function to ensure that the issuance of SP3 truly reflects the principle of legal certainty and does not conflict with the principle of human rights protection.